Profil Glukosa Darah, Lipid dan Visualisasi Pulau Langerhans sebagai Imunoreaktor Insulin dan Glukagon pada Pankreas Tikus (rattus norvegicus) Obesitas Menggunakan Teknik Imunohistokimia - Dela Ria Nesti; Ahmad Baidlowi (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2017)
Obesity is not concerned as specific congenital disorder or derived lipid metabolism disorder recently, but more to bod yinability to handle the increase of nutrition intake caused by behavioral changes. Langerhans Islet is a section in the pancreas which play crucial role in producing and regulating metabolism hormones, insulin and glucagon. This research was conducted to observe blood glucose and lipid profile and to visualize Langerhans Islet in rat pancreas which were induced obesity and compared it with normal ones. Ten of male non-genetic obese four weeks old Winstar rats were divided into two groups, normal (K) and induced with obesity (O). Blood plasma samples were collected to determine blood glucose and blood lipid profile. Pancreas (regio splenic) samples were collected and fixated with Bouin solution, blocked by paraffin and cut with 5 μm thickness. Histology preparats were stained with Hematoxylin-Eosin and Immunohistochemistry (IHC) is determined with Labeled Sterptavidin-Biotin (LSAB) method. Staining is act as visual detector with will be analyzed descriptively and quantitatively. The data of Obesity group showed that blood glucose level is 88.59 ± 1.77 mg/dl, blood cholesterol level is 160.62±3.52 mg/dl, triglycerides level is 98.61±2.66 mg/dl, HDL level is 44.68±2.25 mg/dl and LDL level is 67.51±1.81. Pancreas’s topography in obese group spread into three regions, which are: gastrium, duodenum and lien. Langerhans Islet morphology shaped oval and polygonal also surrounded by fine filaments and blood capillary. Insulin and glucagon immunoreactive cell’s morphology in obesity group shaped irregular polygonal with round/oval nucleus placed in central/peripheral. Langerhans Islet’s in obesity group has diameter (154.38±65.56) μm, circumference (373,51±146,69) μm and volume 3241105.96 μm3. Obesity induced rat showed the increase in cholesterol level, triglycerides level, LDL level, blood glucose level and Langerhans Islet’s diameter, volume and circumference compared to normal ones (P<0.05). Decrease of HDL, topography and morphology of pancreas in obesity induced rat did’t showed significant changes compared to normal ones.